Management Restoration Plans for Coastal Villages - Rudianto Rudianto; Edi Susilo; Supriyatna Supriyatna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
The village is located in the coastal area up to this time has decreased the quality of the coastal environment either caused by the process of natural or anthropogenic processes. Coastal damage Persistent will affect people's lives. Based on studies conducted by Rudianto (2013) and continued research by Rudianto (2014) on the institutional model for implementing the strategy, the resulting output coast of research called restoration plan for coastal villages or R2DP coastal villages.The objective of R2DP is helping the village administration to alleviate the problems of coastal areas. R2DP is a guideline that will be used by the village government based on a legal framework called the village regulations.The method used to compile R2DP is descriptive method. By using the method of Miles and Huberman (1984) used data reduction techniques. This technique is to pick and choose which data is critical to focus on the purpose of research.the results of research to produce findings about the restoration plan or a coastal village called R2DP. The essence of the mechanism and procedure R2DP is doing the restoration work by using institutions as a means of restoration.